ANALISIS MUATAN SASTRA (PUISI) ANAK DALAM BUKU TEMATIK SISWA SD KURIKULUM 2013 SEBAGAI PEMBENTUK KARAKTERISTIK KEPRIBADIAN ANAK: TINJAUAN ANALISIS STILISTIK - Dirneti Dirneti; Tisrin Maulina Dewi; Edi Kurniawan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Literary work is the result of an author's imagination through the medium of language. One form of literary works is poetry. As a literary work, poetry is bound to lines and stanzas. In this study, we discussed the problem of how the content of children's literature (poetry) contained in the 2013 curriculum thematic book of elementary school in shaping the students’ personality characteristics viewed from stylistic analysis. The purpose of the study was to determine the stylistics of children's poetry contained in the 2013 curriculum thematic books of elementary school. The type of this research was qualitative research using descriptive method. This research was in the form of a documentation study, which analyzed the forms of poetry contained in the thematic books of elementary school. Thus, the object of this research was these forms of poetry. Based on the results of data analysis, it was found that the children's poetry contained in elementary school students' books used several sound elements, such as rhyme, alliteration, assonance, anaphora, epanalepsis, mesodiplosis, and onomatopoeia. Meanwhile, the use of diction found in the book was in the form of Arabic diction. Then, the use of images was in the form of images of sight, hearing, smell, and taste while the figures of speech used in this book were personification, hyperbole, metaphor, and simile. Then, it was also found several language deviation, such as morphological, syntactic, and graphological deviations. The forms of children's poetry contained in the thematic books of elementary school weredesigned in accordance with the characteristics of children's poetry. This was seen from the way the elements of sound, diction, figure of speech, images, and language deviations are used.